2019
DOI: 10.3389/fbioe.2019.00065
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a Deep-Learning Method Based on the Classification of Images Generated by Parameterized Deep Snap a Novel Molecular-Image-Input Technique for Quantitative Structure–Activity Relationship (QSAR) Analysis

Abstract: Numerous chemical compounds are distributed around the world and may affect the homeostasis of the endocrine system by disrupting the normal functions of hormone receptors. Although the risks associated with these compounds have been evaluated by acute toxicity testing in mammalian models, the chronic toxicity of many chemicals remains due to high cost of the compounds and the testing, etc. However, computational approaches may be promising alternatives and reduce these evaluations. Recently, deep learning (DL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 159 publications
(204 reference statements)
0
60
0
Order By: Relevance
“…We have previously shown that hyperparameters in the DeepSnap-DL process affect the performance of prediction models [47][48][49]. Therefore, three main hyperparameters-solver types (STs), batch sizes (BTs), and learning rates (LRs)-in the DeepSnap-DL process were preliminarily optimized using the input data of 201 chemical compound structures.…”
Section: Optimization Of Hyperparameters In the Deepsnap-dl Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that hyperparameters in the DeepSnap-DL process affect the performance of prediction models [47][48][49]. Therefore, three main hyperparameters-solver types (STs), batch sizes (BTs), and learning rates (LRs)-in the DeepSnap-DL process were preliminarily optimized using the input data of 201 chemical compound structures.…”
Section: Optimization Of Hyperparameters In the Deepsnap-dl Approachmentioning
confidence: 99%
“…By using the resulting image data as input, a prediction model can be classified and constructed by deep learning (DL); thus, we refer to the method as DeepSnap-DL. In addition, we recently reported that the high performance of prediction models of molecular initiating event (MIE) activity for the AOP can be constructed by optimizing hyperparameters and adjusting input data preparation [47][48][49].…”
Section: Introductionmentioning
confidence: 99%
“…The understanding of chemical systems, and the respective underlying behavior, mechanisms and dynamics, is currently facilitated by the development of descriptive, interpretative, and predictive models, i.e., approximations that represent the target system or process. Applications of such models have included the (i) optimization of reaction parameters and process conditions, e.g., changing the type of reagents, catalysts, and solvents, and also varying systematically, concentration, addition rate, time, temperature, or solvent polarity, (ii) suggestion of new reactions based on critical functional groups, (iii) prediction of reaction/catalyst design, and optimization of heterogeneous/homogeneous catalytic reactions, (iv) acceleration and discovery of new process strategies for batch reactions, (v) establishment of trade-offs in the reaction rate and yield of organic compounds, (vi) description and maximization of the production rate and conversion efficiency of chemical reactions, (vii) prediction of the potential toxicity of different compounds, and also the (viii) rational design of target molecules and guided exploration of chemical space (Kowalik et al, 2012;Zielinski et al, 2017;Häse et al, 2018;Min et al, 2018;Zhou et al, 2018;Ahn et al, 2019;Choi et al, 2019;Gromski et al, 2019;Matsuzaka and Uesawa, 2019).…”
Section: Machine Learning For Optimization: Challenges and Opportunitiesmentioning
confidence: 99%
“…Deep learning (DL) approaches can also be particularly useful to solving a variety of chemical problems, including compound identification and classification, and description of soft matter behavior (Huang et al, 2018;Jha et al, 2018;Jørgensen et al, 2018b;Popova et al, 2018;Segler et al, 2018;Zhou et al, 2018;Chandrasekaran et al, 2019;Degiacomi, 2019;Elton et al, 2019;Ghosh et al, 2019;Mater and Coote, 2019;Matsuzaka and Uesawa, 2019;Xu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…21,22 For example, CNN models have proven the ability to identify brain tumors in magnetic resonance images (MRI) faster and more accurately than the state of the art tools and can identify the pancreas in computerized tomography (CT) images, both of which are challenging analysis problems because of anatomical variability. 10,11 In chemistry, CNN models are being trained using 2D and 3D images of molecular structure for quantitative structure-activity relationship (QSAR) modeling to predict toxicity 23 and to predict therapeutic use classes of drugs. 24 CNN models have also been trained to assign surface-enhanced Raman spectroscopy (SERS) spectra to classes of metabolites and to assign bundles of SERS spectra (8 × 8 pixel hyperspectral images) to the concentration of rhodamine 800 dye at femtomolar concentrations for single molecule detection.…”
Section: Image Analysis Via Convolutional Neural Network (Cnn)mentioning
confidence: 99%